3D Chiral Plasmonic Metamaterials Fabricated by Direct Laser Writing: The Twisted Omega Particle. Issue 16 (16th June 2017) - Sakellari, Ioanna; Yin, Xinghui; Nesterov, Maxim L.; Terzaki, Konstantina; Xomalis, Angelos; Farsari, Maria
Abstract : The plasmonic version of a 3D chiral meta‐atom which consists of a loop‐wire structure, namely the so‐called twisted omega particle, is experimentally realized. The structure is fabricated by direct laser writing and subsequent electroless silver plating, a novel technique capable of producing truly 3D photonic nanostructures. In this case, the metallic wire of finite length supports an electric dipole resonance, whereas the loop acts as a split‐ring resonator which exhibits a magnetic dipole resonance, leading to the separation of right‐handed circularly polarized light and the left‐handed one. The arising optical activity is discussed in terms of a single oscillator model system used classically to describe the generation of natural optical activity in chiral media, and it is shown that the twisted omega particle acts as its exact plasmonic analogue. Abstract : Electroless silver plated twisted omega particles fabricated by direct laser writing are presented. In this case, the metallic wire acts as a small electric dipole antenna, whereas the loop acts as a split ring resonator which exhibits a magnetic dipole resonance, leading to the separation of right‐handed circularly polarized light and the left‐handed one.